Pengaruh Sistem Informasi Akuntansi Penjualan Dan Pengendalian Internal Terhadap Efektivitas Pengendalian Piutang Pada PT. Sentral Medika Indonesia Semarang - Anindita Emma Rahmawati; Batista Sufa Kefi (Jurnal Ekonomi Manajemen Akuntansi, 2022)
This study aims to determine the effect of sales accounting information systems and internal control on the effectiveness of controlling accounts receivable at PT.Sentral Medika Indonesia Semarang. The population in this study were all employees of PT. Sentral Medika Indonesia Semarang with a total of 60 employees, while the sample taken using purposive sampling method is a total of 53 employees who work in the accounting department, sales department, warehouse department, marketing department, manager and president director. . The data analysis tool in this study used multiple linear regression. The results show that the sales accounting information system has a positive and significant effect on the effectiveness of controlling accounts receivable, it can be seen from the t-count value which is greater than the t-table value of 3.016> 1.679, and the significance value of 0.004 is smaller than 0.05, so the hypothesis one accepted. Internal control has a positive and significant effect on the effectiveness of receivables control, it can be seen from the t-count value which is greater than the t-table value, namely 4.242 > 1.679, and the significance value of 0.000 is smaller than 0.05, so hypothesis two is accepted. This means that the higher the company's sales accounting information system and internal control applied in the company, the effectiveness of the internal control carried out by PT. Central Medika Indonesia Semarang will continue to increase.